ANALISIS KANDUNGAN MERKURI (Hg) PADA PADA EKOSISTEM SUNGAI WAELATA DAN SUNGAI ANAHONI YANG TERDAMPAK AKTIFITAS PERTAMBANGAN EMAS DI PULAU BURU, MALUKU - ., Irsan; Male, Yusthinus T.; Selanno, Debby A. J. (CHEMISTRY PROGRESS, 2020)
Sungai Waelata dan Sungai Anahoni merupakan dua sungai tempat beroperasinya trommel untuk pengolahan material emas Gunung Botak dan Gogrea. Melalui aliran sungai, limbah merkuri hasil pengolahan trommel terangkut dan terbawa ke muara yang pada akhirnya akan mencemari perairan laut Teluk Kayeli. Kerang Polymesoda erosa merupakan salah satu jenis kerang yang sering digunakan dalam pemantauan logam berat merkuri, terutama pada wilayah muara sungai. Penelitian ini bertujuan untuk menganalisis kadar logam berat merkuri(Hg) pada air, sedimen dan kerang Polymesoda erosadi Muara Sungai Waelata dan Sungai Anahoni Kabupaten Buru. Hasil penelitian menunjukan konsentrasilogamberat merkuripada air di Muara Sungai Waelata dan Sungai Anahoni tidak terdeteksi di semua stasiun penelitian dan dibawah baku mutu air laut untuk biota laut berdasarkan Kepmen LH No. 51 Tahun 2004 sebesar 0,001 ppm. Konsentrasilogamberat merkuripada sedimenmemilikikisaranrataratasebesar0,1340,874ppm dan dibawah baku mutu sedimen berdasarkan ANZECC/AMRCANZ (2000) sebesar 1,0 ppm. Konsentrasilogamberat merkuripada kerang Polymesoda erosamemilikikisaranrataratasebesar0,1230,206 ppm dan dibawah Batasan Maksimum Cemaran Logam Berat Dalam Pangan merujuk pada Standar Nasional Indonesia (SNI) No. 7387 Tahun 2009 sebesar 1,0 ppmABSTRACT The Waelata River and the Anahoni River are the two rivers where trommel operates for the processing of gold material from Gunung Botak and Gogrea. By the river, mercury waste from the processing of trommel is transported through estuary which will ultimately pollute the waters of the Kayeli Bay. Polymesoda erosa shells are one type of shellfish that is often used in monitoring heavy metals of mercury, especially in the estuary region. This study aims to analyze the concentration of heavy metal mercury (Hg) in water, sediments and Polymesoda erosa shells in the Waelata River and Anahoni River in Buru Regency. The results showed that the concentration of mercury heavy metals in water in the Waelata River and Anahoni River were not detected at all research stations and were below sea water quality standard for marine biota based on Minister of Environment Decree No. 51 of 2004 which is 0.001 ppm. The concentration of mercury heavy metals in sediments has an average range of 0.1340.887 ppm and is below the sediment quality standard based on ANZECC/AMRCANZ (2000) of 1.0 ppm. The concentration of mercury heavy metals in Polymesoda erosa shells has an average range of 0.1230.206 mg/kg and under the Maximum Limit of Heavy Metal Contamination in Food refers to the Indonesian National Standard (SNI) No. 7387 of 2009 which is 1.0 ppm.